Assisted road remarking system : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Mechatronics at Massey University, Turitea, New Zealand - Cameron, Mark (Massey University, 2012)
Roads are used in every part of the world and where there are roads, there are almost always road markings guiding the users of the roads in what they can and cannot do. The process of road marking involves first painting the lines then covering them with small glass beads. This process need to be repeated frequently, depending on the wear of the markings. The remarking of existing lines is complicated and difficult to become proficient in. What is wanted is an assisted road remarking system that will help road markers in their remarking duties and combat some of the problems they face. Creating an assisted remarking system will make it easier to operate a truck. This means it will be easier to move from one truck to another and also it will be easier to train someone up to do the job, eliminating the long teaching period. It will potentially increase the accuracy of the markings as well. In addition it allows the operators to concentrate on the road ahead improving safety and also the speed that remarking can occur. All of these add up to a significant cost saving. This project was split up into two major sections: sensing, and control and actuation. Research was carried out into existing technologies and processes that may be useful. An algorithm was developed using the radon transform to detect existing lane markings by analysing images acquired via a CCD camera. Also developed was a control system for the actuation of the spray nozzle, this was created by modelling the entire system. Through testing the overall system can position an actuator over a line accurately and fast. It can detect a line in a variety of conditions and at various qualities. The actuator moves smoothly and quickly to where it needs to be without any sudden changes in direction. The system that was designed would be of great aid to a road marker and would improve the quality and speed that remarking can be carried out at. It would also allow faster training, improved safety, and cost savings.
Keywords: Road marking; Image processing; Optical sensors; Road marking equipment